Evaluation of the prevalence of enterotoxigenic Bacteroides fragilis and the distribution bft gene subtypes in patients with diarrhea - Akpinar, Mehtap; Aktas, Elif; Coemert, Fuesun; Kuelah, Canan; Suembueloolu, Vildan (Anaerobe, 2010)
The aim of this study was to determine the prevalence of enterotoxigenic Bacteroides fragilis (ETBF) in the patients with diarrhea in our region and to assess the association between diarrhea and bft gene subtypes. The presence of ETBF and bft gene subtypes were investigated in 200 stool samples from patients with diarrhea, diagnosed as gastroenteritis, which were sent to Clinical Microbiology Laboratory at Zonguldak Karaelmas University, Training and Research Hospital and in 200 stool samples from age-matched healthy subjects between April 14, 2009 and October 28, 2009. Nested – polymerase chain reaction was used to detect the presence of bft gene directly from stool samples. The bft gene subtypes were determined by PCR in case of ETBF detection. The presence of bft gene was detected in 29 (15%) of patients and 27 (14%) of control group. bft-1 and bft-2 were found in 24 and five stool samples from 29 diarrheic patients with ETBF, respectively. Among 27 control patients with ETBF, bft-1 and bft-2 were found in 24 and three samples, respectively. No bft-3 subtypes were identified in our study. ETBF was found as a single pathogen in 9% of the patients with diarrhea, while there was an accompanying pathogen in 6% of the patients. The proportion of coinfection with another pathogen among ETBF positive patients was 38%. Cooccurance with ETBF was present in nine of 18 patients with Rotavirus and two of five patients with Entamoeba histolytica. In conclusion; there was no statistically significant difference between the prevalence of ETBF in diarrheal patients and that of the control group. When the patients and controls were compared for each age group, no statistically significant difference in ETBF rates was found. There was no significant difference between groups with respect to bft subtypes; bft-1 was identified as the most common subtype. The rate of coinfection of ETBF and Rotavirus was high.